Society and Education in the Early of XXIth Century: Integration of Tradition and Innovation - EGORYCHEV, Alexander Mikhailovich; MARDOCHAEV, Lev Vladimirovich; RYBAKOVA, Anna Igorevna; FOMINA, Svetlana Nikolaevna; SIZIKOVA, Valeria Viktorovna (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
The purpose of this study is to attempt to identify the existing link in the development of society, as the macro-and national education systems and to justify their particular determinacy. Also to show and to justify the role of the historical heritage of any country of the world community (philosophical, socio-cultural, educational) in the construction of modern national education system. In their study, the authors stand on methodological position, which is expressed in the fact that the education system, as a basic social institution of the state and society, determines their progressive development and acts as a mechanism for reasonable regulation of the national tradition and innovation.